LEARNING INTEGERS WITH REALISTIC MATHEMATICS EDUCATION APPROACH BASED ON ISLAMIC VALUES - Muslimin Muslimin; Ratu Ilma Indra Putri; Zulkardi Zulkardi; Nyimas Aisyah (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2020)
Mathematical learning not only produces students who succeed in mathematical and procedural calculations but also develops religious thinking. Realistic mathematics education with the context of Islamic values makes students can imagine, which is one of the right ways to develop the skills of students’ creativity, collaboration, and communication. This study aims to describe the learning trajectory that can help students understand integers with a realistic mathematics education approach based on Islamic values. It is hoped that student responses are positive, meaningful, and enjoyable. This research uses the design research method, which is a form of a qualitative approach. There are three stages in this research, namely: preliminary design, experimental design, and retrospective analysis. The results showed that the Hypothetical Learning Trajectory (HLT) trial with an Islamic value-based context showed significant progress based on student responses. Initially, students had difficulty understanding integers, but they felt delighted to follow the learning process along with the habituation. The HLT technique used in habituation was through pilot experiments, followed by teaching experiments. Students respond very positively and are happy to follow it by seeing the very significant development of their abilities during the learning process.